Different Types of Diatoms Seen in the River Narmada in India - Arushi Chawla1 , Dhwani Patel2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To determine the different types of diatoms present in the waters of River Narmada flowing through5 distinct cities of India and ending into the Arabian Sea. Different types of Diatoms were observed withchange in the course of water. Objective: The study shall assist to determine the different types of diatomspresent in the river Narmada. Materials and Method: The study does not require any special instrumentsand the technique used to extract the diatoms from the waters is also very simple to perform. In this studythe acid digestion technique is not used but the technique is slightly modified in order to prevent the damageto the walls of the diatoms. Result: Various types of diatoms were seen and the diatoms present in the watercollected from different cities of India are found to be different including the species unique to the area.Conclusion: The study describes the type of diatom present in the water of river Narmada collected fromdifferent places.